PENERAPAN PENDIDIKAN AGAMA KRISTEN REMAJA DALAM KELUARGA DI GBI ROCK PANTAI INDAH KAPUK JAKARTA - Supangat , Febe; Zara, Fenti; Pieter, Roy (STT KINGDOM BALI, 2024)
This research aims to describe: 1.).How is the understanding of the meaning of Christian Religious Education for adolescents by parents at GBI ROCK Pantai Indah Kapuk Jakarta? 2.)How is the understanding of the role of parents in the implementation of Christian Religious Education for adolescents in the family by the parents of GBI ROCK Pantai Indah Kapuk Jakarta? 3.) How is the implementation of Christian Religious Education for adolescents by parents in the family of GBI ROCK Pantai Indah Kapuk Jakarta? This research uses qualitative methods. The object of this research is the Application of Christian Religious Education for Adolescents in the Family at Gbi Rock Pantai Indah Kapuk Jakarta. Data collection techniques using observation methods, documentation studies with respondents 10 parents who have teenage children at GBI ROCK Pantai Indah Kapuk Jakarta. Data analysis uses data condensation, data display (data presentation) and conclusion drawing/verification (conclusion drawing/verification) methods. Data validity testing uses credibility test and data dependability test. The results showed that respondents, namely parents at GBI Rock Pantai Indah Kapuk, all understood the meaning and purpose of Christian Religious Education but were not fully in accordance with the theoretical construct; Explaining the role of parents in the implementation of Adolescent Christian Religious Education in the family is parents as teachers, as educators, disciplining adolescents, role models in the family have not fully explained in accordance with the theoretical contract; The implementation of adolescent PAK in the family is carried out through building a family altar, helping to solve problems, providing spiritual discipline, involving adolescents in church services. Not yet fully explained in accordance with the theoretical contract.